THE BENEFITS OF BILINGUALISM AMONG SCHOOLCHILDREN - Ismailova Fayzakhan Mustafa kizi (Modern American Journals, 2025)
The article examines the main advantages of bilingualism among schoolchildren in terms of cognitive, academic, cultural, social and psychological development. It notes the positive impact of bilingualism on the development of critical thinking, academic performance, intercultural communication and adaptive abilities of children. The role of bilingualism in the formation of tolerance, self-confidence and competitiveness in the educational and professional spheres is emphasized. Particular attention is paid to the need to support bilingualism in the educational system.
Keywords: Bilingualism, schoolchildren, cognitive abilities, academic performance, intercultural communication, tolerance, education, language development, social adaptation.